Current and future on definitive concurrent chemoradiotherapy for inoperable locally advanced esophageal squamous cell carcinoma - Xie, Renxian; Cai, Qingxin; Chen, Tong; Huang, Hongxin; Chen, Chuangzhen (Frontiers in Oncology, 2024)
Esophageal squamous cell carcinoma (ESCC) is an aggressive and fatal disease that is usually diagnosed when the chances for surgical intervention has been missed. Definitive concurrent chemoradiotherapy (dCRT) is the first choice of treatment for inoperable locally advanced esophageal squamous cell carcinoma (LA-ESCC). Nevertheless, the local recurrence rate for esophageal cancer patients undergoing dCRT remains high at 40-60%, with a 5-year overall survival rate of solely 10-30%. Immunotherapy in combination with dCRT is a promising treatment for inoperable LA-ESCC, for that improved long-term survival is expected. The present review provides a comprehensive overview of the evolutionary trajectory of dCRT for LA-ESCC, delineates notable relevant clinical studies, addresses unresolved concerns regarding the combination of dCRT with immunotherapy, and highlights promising directions for future research. When dCRT is combined with immunotherapy, the following aspects should be carefully explored in the future studies, including the optimal irradiation dose, segmentation scheme, radiotherapy technique, timing, sequence and duration of radiotherapy, and the selection of chemotherapeutic and immunologic drugs. In addition, further investigations on the mechanisms of how dCRT combined with immunotherapy exerts synergistic anti-tumor effects and molecular biomarkers ensuring precise screening of ESCC patients are needed.